Provisional Measures in Brazil and their distortion in the context of the pandemic: an analysis with emphasis on the unconstitutionality of provisional measures nº 979∕2020 and nº 1.068∕2021 (Research, Society and Development, 2022)
The arrival of the COVID-19 in Brazil made it necessary for a fast and effective government action to contain the socioeconomic impacts caused by the pandemic. In this context, the Provisional Measure presents itself as a normative instrument that the Constitution made available to the President of the Republic to be used in urgent and socially relevant situations. Accordingly, it appears that the pandemic, since its inception, was the main reason for the significant increase in the number of Provisional Measures in Brazil. Thus, the present work aims to study and analyze the Provisional Measure in Brazil and its use in the context of the pandemic, emphasizing the unconstitutionality of Provisional Measures nº 979/2020 and nº 1.068/2021. The methodology used consists of bibliographic research, based on books, academic articles, jurisprudence and rules regarding the subject, besdies a survey of the amount and situation of the Provisional Measures edited in the first three years of President Jair Bolsonaro's government. Therefore, it is concluded that although the pandemic has provided a favorable legal environment for the use of this instrument on a regular basis, it was also used to motivate the edition of some unconstitutional measures, such as the Provisional Measures specifically addressed in the study. The distortion of the use of this legal act in the context of the pandemic demonstrates the fundamental importance of the exercise of control of these acts by the Legislative Power and the Judiciary, so that the independence and harmony between the three powers is guaranteed.